Development of Carboxymethyl Cellulose and Graphene Filled Polypropylene Composites: Hybridization of Natural and Nanofillers - Tuna, Sibel; Sen, Ibrahim (Wiley-V C H Verlag Gmbh, 2025)
Polymeric composites have become important in materials engineering thanks to their advanced properties and potential for versatile applications. In this study, the effects of reinforcing polypropylene (PP), a widely used thermoplastic with carboxymethyl cellulose (CMC), a natural additive, and graphene (Gr), a nanoadditive on its performance were investigated. While CMC offers advantages such as lightness and biodegradability, the goal of Gr is to achieve high mechanical and thermal performance in the composite. Using maleic anhydride as a compatibilizing agent improves the compatibility between the fillers and the matrix. Physical, structural, thermal, mechanical and morphological characterization of the injection-moulded composite structures revealed slight increases in density and hardness values, as well as enhanced crystallization behavior, thermal stability, and degree of crystallinity. The tensile and flexural properties generally improved with increasing filler content and microstructural analysis confirmed the good distribution and high interaction of the fillers in the matrix. Overall, hybrid structures incorporating CMC/Gr fillers in a PP matrix were identified as a promising alternative for multifunctional and sustainable engineering applications.
Keywords: Carboxymethyl Cellulose; Graphene; Hybrid composites; Polypropylene composites; Synergistic effect